CHILD-FRIENDLY LIBRARY MANAGEMENT AS A STRATEGY TO STRENGTHEN READING LITERACY IN ISLAMIC ELEMENTARY EDUCATION - Choirun Nisa; Muhammad Khoirurrosyid (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aimed to analyze how child-friendly library management can serve as a strategic approach to strengthen reading literacy in Islamic elementary education. The research was conducted at SD Al-Firdaus Surakarta, an Islamic primary school integrating literacy and moral education. Using a qualitative descriptive design with a single case study approach, data were collected through observation, semi-structured interviews, and document analysis involving the principal, librarian, teachers, and students. The data were analyzed using Miles and Huberman’s interactive model, comprising reduction, display, and conclusion drawing.The results revealed that child-friendly management was implemented through three interrelated dimensions: the physical design of the library, collaboration among teachers, the librarian, and parents, and the integration of literacy programs grounded in Islamic values. The library provided accessible reading spaces, diverse collections, and a digital library platform that increased students’ engagement and reading frequency. Collaborative literacy programs such as Gemar Baca Buku and Home Reading successfully nurtured students’ reading motivation and moral reflection.The study concludes that a child-friendly library, when managed as a holistic learning ecosystem, can significantly enhance reading literacy while aligning with the ethical and cultural context of Islamic education. This research contributes to the field of educational management by introducing a culturally responsive model that integrates global child-centered principles with local religious and pedagogical values.